2004
DOI: 10.1016/j.physa.2004.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis mediated by a domain wall motion

Abstract: The position of an interface (domain wall) in a medium with random pinning defects is not determined unambiguously by a current value of the driving force even in average. Based on general theory of the interface motion in a random medium we study this hysteresis, different possible shapes of domain walls and dynamical phase transitions between them. Several principal characteristics of the hysteresis, including the coercive force and the curves of dynamical phase transitions obey scaling laws and display a cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…After the seminal theoretical works of Natterman and coworkers [37][38][39][40] , experiments carried out mainly by AC susceptibility measurements corroborated some of their predictions 41 . The theoretical works [37][38][39][40] generically study the response of DWs to AC fields and in particular predict different magnetic hysteresis loops as a function of the amplitude and frequency of an applied oscillating magnetic field, H(t) = H 0 sin ωt. It is predicted that at low frequencies ω < γH p /L and for amplitudes such that H 0 > H ω the AC behavior is well described by applying the dynamic equation holding in the DC case.…”
Section: Introductionmentioning
confidence: 71%
“…After the seminal theoretical works of Natterman and coworkers [37][38][39][40] , experiments carried out mainly by AC susceptibility measurements corroborated some of their predictions 41 . The theoretical works [37][38][39][40] generically study the response of DWs to AC fields and in particular predict different magnetic hysteresis loops as a function of the amplitude and frequency of an applied oscillating magnetic field, H(t) = H 0 sin ωt. It is predicted that at low frequencies ω < γH p /L and for amplitudes such that H 0 > H ω the AC behavior is well described by applying the dynamic equation holding in the DC case.…”
Section: Introductionmentioning
confidence: 71%
“…The analytically categorization of the HLs propounded by Lyuksyutov et al [37]. In addition to this, the two other works about the relations between the domain wall motion and the dynamic hysteresis, are published by approximately the same collaborators [38,39]. In the current year, Idigoras et al [25] have demonstrated that the bias field behaves as if it is the conjugate field of the DOP near the DTP for ferromagnets.…”
Section: Introductionmentioning
confidence: 95%
“…The top two curves are the naive power law (equation 24, obviously not correct) and the correct law (equation 26). We compare with the relation between the avalanche size S and the duration T (equation 19), which has the same combination of critical exponents S ∼ (1/T ) −1/σνz . We also show that the energy spectrum of individual large avalanches is proportional to S and has the same power law in frequency ω as that of the entire time series, so we plot P (ω|S)/S for a variety of avalanche sizes S.…”
Section: E Energy Spectrummentioning
confidence: 99%
“…Many systems exhibit similar crackling noise: when pushed slowly they respond with discrete events of a broad range of sizes. 19 The earth responds (108) with violent and intermittent earthquakes as two tectonic plates rub past one another. A piece of paper (4) (or a candy wrapper at the movies (109; 110)) emits intermittent, sharp noises as it is slowly crumpled or rumpled.…”
Section: Systems With Avalanchesmentioning
confidence: 99%